Legal Protection For Consumers In After-Sale Services For The Use Of Electronic Products - Ripamole, Bebi Sartika; Kantikha, I Made; Markoni, Markoni; Subiyakto, Achmad Edi (LEGAL BRIEF, 2025)
The development of technology in the field of electronics is progressing rapidly. The high demand from consumers for electronic products creates an opportunity for business actors to compete in producing and marketing electronic products. To ensure that the circulating electronic products meet the regulated standards, the government has established rules regarding after-sales services that must be provided by business operators. In practice, there are still consumers who feel disadvantaged by after-sales services, which include limited spare parts availability, unclear information, and complicated warranty claim processes. The purpose of this writing is to analyse the protection that can be provided to consumers for losses incurred after the use of electronic products and how to resolve disputes over the losses experienced. From the research conducted, it was found that consumers are entitled to compensation either in the form of a refund equivalent to the price of the product purchased or a replacement unit that is appropriate and similar to the consumer's product, as well as compensation for losses that may arise due to inadequate after-sales service. If the business operator fails to fulfil their obligations, the consumer can file a compensation claim against the business operator outside of court, namely through the BPSK, and if the BPSK resolution is unsatisfactory, the consumer can file their lawsuit through the general court. The conclusion drawn from this research includes the obligation of business operators to fulfil consumer rights for losses caused by inadequate after-sales service of electronic products, as well as the resolution actions that consumers can take to obtain their rights appropriately